Systematic Review: Antifungal Efficacy of Morinda Citrifolia Against Candida Albicans - Purnama, Intan; Susilawati; Dwi Prasasty, Gita (Sriwijaya Journal of Medicine, 2025)
Candidiasis, caused by Candida species, remains a significant global health concern, with oral and vulvovaginal forms prevalent among immunocompromised populations and women, respectively. Increasing antifungal resistance, particularly among non-albicans species, underscores the need for novel therapeutic options. This systematic literature review assesses the antifungal efficacy of Morinda citrifolia (noni fruit) against Candida albicans. Utilizing the PRISMA protocol, we analyzed studies from Scopus, ScienceDirect, PubMed, and Google Scholar databases published between 2014 and 2024. Seven in vitro studies were included, examining the inhibitory effects of M. citrifolia extracts on C. albicans. Findings indicate that M. citrifolia exhibits significant antifungal properties, attributed to its bioactive compounds such as scopoletin and flavonoids, which disrupt fungal cell membranes. The effectiveness of M. citrifolia is concentration-dependent, with higher concentrations yielding greater antifungal activity. Given the increasing resistance to conventional antifungals, in vitro studies suggest that M. citrifolia may be a promising alternative, warranting further in vivo and clinical investigations to substantiate its therapeutic potential.